2012
DOI: 10.1002/pssc.201200390
|View full text |Cite
|
Sign up to set email alerts
|

High performance imaging of relativistic soft X‐ray harmonics by sub‐micron resolution LiF film detectors

Abstract: The spectrum variation and the coherent properties of the high‐order harmonics (HOH) generated by an oscillating electron spikes formed at the joint of the boundaries of a cavity and a bow wave, which are created by a relativistically self‐focusing laser in underdense gas jet plasma, are investigated. This new mechanism for HOH generation efficiently produces emission from ultraviolet up to the XUV “water window” spectral range. To characterize such source in the wide spectral range a diffraction imaging techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The first demonstration of the usage of LiF for HHG was reported in [9], using relativistic HHG in the range of 80-150 eV. While the relatively low signal-to-noise ratio due to the XUV energy per shot and source stability was not enough to demonstrate high resolution imaging, this study showed single-shot acquisition was possible in the XUV.…”
Section: Introductionmentioning
confidence: 76%
“…The first demonstration of the usage of LiF for HHG was reported in [9], using relativistic HHG in the range of 80-150 eV. While the relatively low signal-to-noise ratio due to the XUV energy per shot and source stability was not enough to demonstrate high resolution imaging, this study showed single-shot acquisition was possible in the XUV.…”
Section: Introductionmentioning
confidence: 76%
“…To model the intensity distribution in the diffractive image (for details of the algorithm see [72]) we used a harmonic spectrum at the observation angle of 8°, figure 14(c), obtained in the 2D PIC simulation, see later in section 5. Only harmonic orders above ten are taken into account, corresponding to the LiF sensitivity threshold.…”
Section: Resultsmentioning
confidence: 99%
“…This cusp singularity is situated near the laser pulse head, and is strongly driven by the laser field. The accelerated motion of the electrons in the singularity leads to high-frequency radiation, while the singularity sharpness ensures constructive interference, producing a bright coherent x-ray pulse [17,[22][23][24][25][26][27] termed Burst Intensification by Singularity Emitting Radiation (BISER) [28]. BISER has an unprecedentedly small source size: sub-m measured directly (limited by the resolution of employed xray optics) and down to 10 nm predicted by the PIC simulations [28].…”
Section: Introductionmentioning
confidence: 99%